2005
DOI: 10.1128/jvi.79.3.1581-1594.2005
|View full text |Cite
|
Sign up to set email alerts
|

Involvement of Clathrin-Mediated Endocytosis in Human Immunodeficiency Virus Type 1 Entry

Abstract: Productive entry of human immunodeficiency virus (HIV) is believed to occur by direct fusion at the plasma membrane. Endocytic uptake of HIV particles has been observed in several studies but is considered to be nonproductive, leading to virus degradation in the lysosome. We show here that endocytosis contributes significantly to productive HIV entry in HeLa cells by using trans dominant-negative mutants of dynamin and Eps15. Inducible expression of a dominant-negative mutant of dynamin in a CD4-positive HeLa … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

13
161
0
1

Year Published

2005
2005
2016
2016

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 206 publications
(175 citation statements)
references
References 60 publications
(65 reference statements)
13
161
0
1
Order By: Relevance
“…Experiments tracking Reoviruses, transferrin, LDL and labelled CCPs revealed a random initiation behaviour of coated pits, which are only stabilized after cargo binding 30 . For HIV, although direct fusion with the plasma membrane is the main pathway to deliver the capsid into the cytoplasm, a smaller fraction of viruses also infect cells by clathrin-mediated endocytosis 32 . Besides clathrin-or caveolin-mediated endocytosis, various viruses, including Polyoma virus and Herpes Simplex virus (HSV) [33][34][35] , exploit other clathrin-and caveolinindependent entry pathways.…”
Section: Viral Entrymentioning
confidence: 99%
“…Experiments tracking Reoviruses, transferrin, LDL and labelled CCPs revealed a random initiation behaviour of coated pits, which are only stabilized after cargo binding 30 . For HIV, although direct fusion with the plasma membrane is the main pathway to deliver the capsid into the cytoplasm, a smaller fraction of viruses also infect cells by clathrin-mediated endocytosis 32 . Besides clathrin-or caveolin-mediated endocytosis, various viruses, including Polyoma virus and Herpes Simplex virus (HSV) [33][34][35] , exploit other clathrin-and caveolinindependent entry pathways.…”
Section: Viral Entrymentioning
confidence: 99%
“…Co-receptor recognition then leads to conformational changes within the viral transmembrane glycoprotein gp41, which mediates membrane fusion. While productive HIV-1 entry through direct fusion of the virion with the plasma membrane has been well established, we have recently shown that endocytotic uptake of HIV-1 can also contribute to productive infection (Daecke et al 2005;Fackler and Peterlin 2000;Maurin et al 2007). It is difficult to differentiate between different parallel viral-entry pathways or to dissect subsequent steps of the entry process using bulk biochemical and virological analyses, which have been widely used to investigate the HIV-1 entry process.…”
Section: Introductionmentioning
confidence: 99%
“…42,51,52 The principle of this assay is illustrated in Figure 1. HIV-1 pseudoviruses containing b-lactamase fused to the N-terminus of the HIV-1 Vpr (BlaM-Vpr) are produced by coexpressing the BlaM-Vpr and HIV-1 backbone in producer cells, as described in Miyauchi et al 42 HIV-1 Vpr is required to direct BlaM-Vpr incorporation into the viral core.…”
Section: Direct Measurements Of Hiv-1 Fusion With Target Cells By Thementioning
confidence: 99%